The Sensitivity and Specificity of Clinical Examination of the Hemodialysis Arterial-Venous Fistula (AVF) as Compared to Angiography (Global Journal of Medical Research, 2016)
Background and Objectives: Physical examination of the hemodialysis arterial-venous fistula (AVF) is convenient and inexpensive, and can often detect common problems associated with hemodialysis access. Routine systematic physical examination of the fistula by the dialysis staff with each treatment may allow early detection of problems that are commonly associated with mature fistula. This avoiding missed treatments and emergent situations. Dialysis access stenosis is the most common cause of access dysfunction. Physical examination is an important method in the assessment of stenotic lesions. The purpose of this study is to evaluate the two simple maneuvers in physical examination of the AVF (pulse augmentation and pressure assessment inside the fistula and collapsibility of the fistula on arm elevation) and compare them with the gold standard angiography.
Keywords: AVF (arteriovenous fistula); angiography; augmentation of the AVF; collapsibility of the AVF; interventional nephrologist; stenosis of the outflow tra